Predictive performance of the cardiovascular event risk test 2 risk score in hemodialysis patients with ESKD: clinical research : chronic kidney disease - Witoslawska, Angelika; Drechsler, Christine; Duarte, Kevin; Girerd, Nicolas; Zannad, Faiez; Rossignol, Patrick; Kleber, Marcus E.; Scharnagl, Hubert; Wanner, Christoph; März, Winfried; Laaksonen, Reijo (Clinical journal of the American Society of Nephrology, 2025)
Key Points  - - The Cardiovascular Event Risk Test 2 (CERT2) risk score effectively stratified patients undergoing hemodialysis patients on the basis of their risk of major adverse cardiovascular (CV) event, CV death, and all-cause death. - Patients in the highest CERT2 risk category had a two-fold higher risk of major adverse CV event and all-cause death compared with those in the lowest category. - CERT2 risk score shows that novel lipid-based biomarker solution outperforms regular CV risk biomarkers and existing risk scores in dialysis. - - - Background  - ESKD is closely associated with cardiovascular disease (CVD) primarily because of shared underlying conditions, such as diabetes mellitus and hypertension. Increased levels of circulating ceramide lipids have been linked to major adverse events in CVD, as well as to ESKD. Our aim was to investigate the predictive value of the Cardiovascular Event Risk Test 2 (CERT2) risk score in patients with ESKD in identifying patients at an increased risk of major adverse cardiovascular events (MACEs). - Methods  - This study combines data from 2311 patients from the A Study to Evaluate the Use of Rosuvastatin in Subjects on Regular Hemodialysis: An Assessment of Survival and Cardiovascular Events (AURORA) trial and 1137 patients from the Die Deutsche Diabetes Dialyze Studie (4D) trial. Both studies enrolled patients with ESKD undergoing hemodialysis. The CERT2 risk score has been calculated on the basis of quartile stratification of predefined lipid ratios for all the participants. The primary outcome of interest was MACE with additional outcomes of cardiovascular death and all-cause death. - Results  - After adjusting for traditional CV factors and other variables, two-fold higher risk was reported for MACE for patients in the highest risk category (AURORA: hazard ratios [HRs], 1.98; 95% confidence interval [CI], 1.53 to 2.55; 4D: HR, 1.70; 95% CI, 1.23 to 2.34) in comparison with those in the lowest risk category. Similarly, the two-fold higher risk was also observed for all-cause death for patients in the highest risk category (AURORA: HR, 2.14; 95% CI, 1.72 to 2.66; 4D: HR, 1.78; 95% CI, 1.36 to 2.34). In both trials, the CERT2 risk score demonstrated superior predictive performance compared with traditional markers like LDL cholesterol. In the AURORA cohort, the CERT2 risk score outperformed Systematic Coronary Risk Evaluation 2 and atherosclerotic CVD risk estimators in predicting CV outcomes. - Conclusions  - The CERT2 risk score identifies patients with ESKD who are at a higher risk of MACE and all-cause death. These findings highlight the potential of the CERT2 risk score as a novel lipid-based biomarker for CV risk stratification in patients undergoing hemodialysis, offering improved prognostic performance over existing biomarkers and risk scores. - - - - Visual Abstract - - Export